Praktik Konsultasi Pengelolaan Sumber Daya Manusia di PT. Borlindo Mandiri Jaya - Agatha Puji Selvira Pratiwi; Aldian Nur; Anita Maharani (Universitas Mathla'ul Anwar Banten, 2021)
PRACTICE OF HUMAN RESOURCE MANAGEMENT CONSULTING AT PT. BORLINDO MANDIRI JAYA. The purpose of writing this paper is to describe the report on consultative activities as part of community service activities carried out by students in the S2 program to automotive companies in Makassar. The company that is a client is a company that feels there is a problem in the scope of human resource management. The approach taken in community service activities is consultative, where students act as consultants and provide suggestions on what companies should do. The writing method is also used to support this activity, and in this case, the writer uses a survey approach whose purpose is to see a description of employee perceptions about organizational commitment and desire to leave the company. The results obtained are employee perceptions of organizational commitment and the desire to get out quite well, and the authors propose several things that can be pursued by the company.